PENGARUH PROFESIONALISME, MATERIALITAS, DAN RISIKO AUDIT TERHADAP PENGENDALIAN INTERN SERTA IMPLIKASINYA TERHADAP OPINI AUDIT - PATRIANDARI SOEDARSO (Jurnal Akademika, 2018)
This study is purposed to identify and analyze the relationship and influence of professionalism, materiality, and audit risk to internal control and its implications to the audit opinion on the public accounting firm in South Jakarta. Purposive sampling technique are used in this study, and 140 respondents, who are auditors and work in the public accounting firm in South Jakarta, were met the sample criteria. The analytical method used is the Path analysis. The results indicate that the relationship between variables professionalism, materiality and audit risk have a moderate level of relationship. Influence of professionalism, materiality and audit risk simultaneously affect the internal control of 70.9 percent of measurement. While the influence of professionalism, materiality, audit risk, and internal control altogether affect the audit opinion of 74.2 percent of measurement. Keywords: professionalism, materiality, audit risk, internal control, audit opinion